IMPLEMENTASI LESSON STUDY DALAM PEMBELAJARAN IPS DI SMP MUHAMMADIYAH KEMBARAN - Sakinah Fathrunnadi Shalihati (IKIP PGRI Bojonegoro, 2019)
Abstract: Social Study is still considered a boring and less interesting subject in SMP Muhammadiyah Kembaran, it can be seen from the result of the examination in the odd semester in Academic Year of 2017/2018 showing that there were 5 students out of 13 students of the seventh grade who did not pass. The implementation of the lesson study aimed to improve the quality of teacher teaching and students’ participation in learning. Lesson Study that had been implemented is a design in 3 cycles consisting of the activities of planning (plan), implementation (do) and reflection (see). The subjects of Lesson Study observation were social study teacher and students of the seventh grade in the even semester in Academic Year of 2017/2018 with a total of 13 students. Video, photos, discussions and observations were used to analyze the data, which were then analyzed by qualitative descriptive. The results obtained showed that students’ interest and motivation experienced an increase in following social study learning, as evidenced by the increase in students' participation in completing the tasks given by the teacher. Keywords: Lesson Study, Learning, Social Study. Abstrak: Ilmu Pengetahuan Sosial (IPS) masih dianggap Mata Pelajaran yang membosankan dan kurang menarik di SMP Muhammadiyah Kembaran, hal ini dapat dilihat dari hasil ujian pada semester ganjil di Tahun Ajaran 2017/2018 yang menunjukkan bahwa terdapat 5 siswa dari 13 siswa kelas VII yang tidak lulus pada mata pelajaran ini. Pelaksanaan Lesson Study kali ini bertujuan untuk meningkatkan kualitas pengajaran guru dan partisispasi siswa dalam pembelajaran. Lesson Study dilaksanakan dengan desain 3 siklus yang terdiri dari kegiatan perencanaan (plan), implementasi (do), dan refleksi (see). Subjek pengamatan lesson study ini adalah guru IPS dan siswa kelas VII pada semester genap di Tahun Ajaran 2017/2018 dengan total 13 siswa. Video, foto, diskusi dan observasi digunakan untuk menganalisis data, yang kemudian dianalisis dengan deskripsi kualitatif. Hasil yang diperoleh menunjukkan bahwa minat dan motivasi siswa mengalami peningkatan dalam mengikuti pembelajaran IPS, yang dibuktikan dengan partisipassi siswa dalam menyelesaikan tugas yang diberikan oleh guru. Kata Kunci: Lesson Study, Pembelajaran, Ilmu Pengetahuan Sosial